Strengthening the Values of Ahlussunnah wal Jama'ah through Islamic Spiritual Activities at Bina Warga 1 Palembang High School in Fostering Student Tolerance Attitudes - Arib, M. Farhan; Zuhdiyah, Zuhdiyah; Maryamah, Maryamah (Journal of Educational Sciences, 2025)
This study examines the role of Rohani Islam (ROHIS) extracurricular activities at SMA Bina Warga 1 Palembang in strengthening Ahlussunnah wal Jama’ah (ASWAJA) values and shaping students’ tolerance. Despite not being affiliated with NU, the school’s ROHIS program, established in 2018, emphasizes ASWAJA principles through structured daily, weekly, monthly, and annual activities aimed at fostering religious and tolerant attitudes. Using qualitative methods with a case study approach, data were collected via observation, interviews with ROHIS mentors, Islamic education teachers, and participants, as well as documentation. Findings reveal that ROHIS instills ASWAJA values tawasuth (moderation), tasamuh (tolerance), i’tidal (justice), and tawazun (balance) through discussions, interfaith collaborations, and community service. These activities cultivate tolerance by encouraging respect for differences, promoting peace, appreciating kindness, and fostering openness. Key supporting factors include high student participation, institutional support (facilities from the school foundation), and active management. Challenges include some students’ self-centered tendencies, administrative inefficiencies (e.g., unstructured licensing), and logistical issues such as water shortages. The study concludes that ROHIS effectively integrates ASWAJA values into students’ ethical frameworks, despite obstacles, by combining religious education with practical tolerance-building initiatives. This highlights the potential of school-based spiritual programs to address societal diversity while maintaining theological integrity. Recommendations include improving administrative coordination and addressing resource limitations to enhance program sustainability.